2022
DOI: 10.1002/ijc.34060
|View full text |Cite
|
Sign up to set email alerts
|

Impact of noncoding RNAs on cancer directed immune therapies: Now then and forever

Abstract: Accumulating evidence demonstrates that the host genome's epigenetic modifications are essential for living organisms to adapt to extreme conditions. DNA methylation, covalent modifications of histone and interassociation of noncoding RNAs facilitate the cellular manifestation of epigenetic changes in the genome. Out of various factors involved in the epigenetic programming of the host, noncoding RNAs (ncRNAs) such as microRNA (miRNA), long noncoding RNA (lncRNA), circular RNA, snoRNA and piRNA are new generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 163 publications
(261 reference statements)
0
3
0
Order By: Relevance
“…As a type of non-coding RNAs, piRNAs have also been found to play a role in immune modulation and response to cancer. 87 It has been suggested that piRNAs can potentially influence immune cell differentiation, response to inflammation, and even affect tumor immunogenicity. 88,89 Moreover, compared to miRNAs and siRNAs, piRNAs may also potentially possess more advantages (Figure 1), for instance: a.…”
Section: Pirnasmentioning
confidence: 99%
“…As a type of non-coding RNAs, piRNAs have also been found to play a role in immune modulation and response to cancer. 87 It has been suggested that piRNAs can potentially influence immune cell differentiation, response to inflammation, and even affect tumor immunogenicity. 88,89 Moreover, compared to miRNAs and siRNAs, piRNAs may also potentially possess more advantages (Figure 1), for instance: a.…”
Section: Pirnasmentioning
confidence: 99%
“…Recently, immunotherapy has emerged as a potential addition to this standard regimen. This development underscores the need to understand and investigate lncRNAs as they regulate the expression of immunogenic proteins or tumor-associated antigens [ 172 ]. This regulation could stimulate an anti-tumor immune response, enhancing the effectiveness of current immunotherapies.…”
Section: Exploring Strategies For Manipulating Lncrnas To Enhance Ant...mentioning
confidence: 99%
“…DNA methylation, covalent modification of histones and interlinking of non-coding RNAs contribute to the cellular expression of epigenetic changes in the genome. Among the various factors involved in host epigenetic programming, non-coding RNAs (ncRNAs) such as microRNAs (miRNAs), long-stranded non-coding RNAs (lncRNAs), and cyclic RNAs, affect a various cellular processes, such as tumor immunity and cell differentiation ( Roy et al, 2022 ).…”
Section: Anti-tumor Mechanism Of Action Of the Active Ingredients Of ...mentioning
confidence: 99%